A comparative study: exploring the food security in Malaysia and Singapore - Liow, Jia Ying (2023)
This research explores the landscape of food security in Malaysia, delving into essential aspects, obstacles, and prospects. This study compares Malaysia's food security with Singapore because they are neighbouring countries, and the Global Food Security Index (GFSI) indicates that Singapore has a higher ranking. With a primary focus on Singapore for comparison, the study investigates the policies, regulatory framework, and historical trajectory concerning a secure and sustainable food supply in both countries. The findings highlight challenges stemming from political commitment, inadequate funding, and the absence of a dedicated food security law. Additionally, the research probes into the impact of climate change, external factors, and economic hurdles on Malaysia's food security. The study employs a diverse range of data sources, encompassing both primary and secondary outlets. This includes insights gathered from interviews, academic literature, governmental reports, and legal documents. This multifaceted approach aims to offer a thorough and comprehensive exploration of the intricacies surrounding food security in both Malaysia and Singapore. Through expert interviews and a comparative examination with Singapore, the study provides practical insights for policymakers, government bodies, and non-governmental organizations. It advocates for sector-specific inquiries, comparative analyses, and the integration of quantitative research methods in future studies to improve data precision and support evidence-based policy decisions in tackling food security challenges.